Liquid information in the post-truth era - Ramos Chávez, Alejandro (Revista General de Información y Documentación, 2018)
The exponential growth in the term post-truth has emerged due to the global influence of certain relevant political and social processes, as well as the characteristics of the processes by which individuals obtain, generate and exchange information. These processes are increasingly linked to Internet usage and digital social networks. This article aims to analyse the concept of post-truth and contextualise its use and main theoretical problems. Additionally, the article proposes the idea of liquid information – in allusion to Zygmust Bauman’s proposals – as information that is not verified, supported or confirmed; in contrast to information that is solid, understood as information that is documented, reasoned and enriching, and verifies its truth. This analysis considers current sources for obtaining information and generating public opinion.